Sengketa Pencalonan Pemilihan Kepala Daerah Kota Pekanbaru Tahun 2017 - Faridhi, Adrian (Pagaruyuang Law Journal, 2019)
The election of the Regional Head of Pekanbaru in 2017 generally went smoothly, but at the beginning of the implementation of the Pilkada stage there was a nomination dispute between the regional head candidates who did not qualify with the Pekanbaru City General Election Commission (KPU). The nomination failure was the basis of the dispute over the nomination of the regional head, because there was a reason for disability in one of the prospective candidates which resulted in the failure of the candidate to become the regional head candidate for the Pekanbaru City Election in 2017. This research is sociological juridical legal research, in the form of how to deal with applicable laws and regulations are then associated with the reality that occurs in the community. The results of this study were in the form that Pekanbaru City KPU was asked to include the H. Dastrayani Bibra- H. Said Usman Abdullah as a participant in 2017 Mayor and Deputy Mayor Election, the interpretation of disability carried out by the KPU was refuted by the decision on nominating disputes issued by Pekanbaru City Election Supervisory Committee (Panwas). The conclusion in this study is in the dispute over the nomination of the Pekanbaru regional head that the Pekanbaru City Election Commission Decision was canceled with a Decision from the Election Supervisory Agency.